Multiple autism-linked genes mediate synapse elimination via proteasomal degradation of a synaptic scaffold PSD-95 - Tsai, Nien-Pei (2012)
The activity-dependent transcription factor, Myocyte Enhancer Factor-2 (MEF2), induces excitatory synapse elimination in mouse neurons which requires Fragile X Mental Retardation Protein (FMRP), an RNA binding protein implicated in human cognitive dysfunction and autism. We report here that protocadherin-10 (Pcdh10), an autism-spectrum disorders gene, is necessary for this process. MEF2 and FMRP cooperatively regulate the expression of Pcdh10. Upon MEF2 activation, PSD-95 is ubiquitinated by the ubiquitin E3 ligase, murine double minute-2 (Mdm2) and then binds to Pcdh10, which links it to the proteasome for degradation. Blockade of the Pcdh10 -proteasome interaction inhibits MEF2-induced PSD-95 degradation and synapse elimination. In FMRP-lacking neurons, elevated protein levels of eukaryotic translation elongation factor 1-alpha (EF1α), an Mdm2 interacting protein and FMRP target mRNA, sequester Mdm2 and prevent MEF2-induced PSD-95 ubiquitination and synapse elimination. Together our findings reveal novel roles for multiple autism-linked genes in activity-dependent synapse elimination.